TINGKAT KEPUASAN PETERNAK AYAM BROILER TERHADAP POLA KEMITRAAN MODEL CONTRACT FARMING DI KECAMATAN LUBUK DALAM KABUPATEN SIAK (Studi Kasus PT. Mitra Anugerah Satwa) - Opih Muhaemi; Cepriadi '; Kausar ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
This research aims to 1) determine the characteristics of the business and a partnership PT. Mitra Anugerah Animals, 2) analyze the level of satisfaction of broiler breeders in partnership with PT. Mitra Anugerah Animals. The research was conducted in January in District Lubuk In Siak Regency penilayan type is descriptive using quantitative data. Data analysis was performed by descriptive, analytical Costomer Satisfaction Index (CSI) and Importance Performance Analysis (IPA). executed partnership is the core plasma model Contract Farming. The partnership pattern PT. Animal Anugerah Mitra is a closed partnership, farmers are not allowed to sell crops or supply of livestock production facilities of the other party. Company helps the plasma in terms of capital by providing the means of production. This study used seven variables to determine the level of satisfaction of the farmer, After calculation using the Customer Satisfaction Index Customer Satisfaction IndexI known value is 76.18%. This value is based on the satisfaction index of plasma ranch, then Customer Satifaction Index PT. Mitra Anugerah reached 0.76 Animals are in the range of 0.66 to 0.80 in general level of satisfaction of the farmer are the criteria are satisfied. analysis Importance Performance Analysis (IPA) variable quality of the means of production of livestock is in quadrant I (highest priority) that have low performance, variable price contracts sapronak, the role of technical service, and bonuses are in quadrant II (keep achievement) and variable admission procedures partners , delivery schedule and harvesting sapronak broilers are in quadrant IV (redundant). Keywords : Broiler, Contracts Farming, Partnerships